HUBUNGAN ANTARA PERSEPSI SISWA TERHADAP IKLIM SEKOLAH DENGAN MOTIVASI BELAJAR PADA SISWA MADRASAH TSANAWIYAH SARONGGE SUMEDANG - Siti Rohmah; Alfin Ruzhendi; Dadan Nurulhaq (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2009)
Students whom felt that school environment was conducive and according to his/her needs and motivation will have positive image and perception towards their school. This positive perception could be seen that students felt that schooling environment will have full support for their learning progress while following all academic and learning activities at their school have major impact on their progress also—both of which would given great contribution on their participation in learning activities—while also helped them to be more focused and more disciplined. An implementation of fairness on rules, award and punishment were also contributed to the feeling that students felt that they were also part of their school and increasing their sense of belongings to their community—which then would lead and motivate them more to achieve higher achievement both inside and outside of school environment.Sample population in this research are students of Madrasah Tsanawiyah Sarongge which consisted of 70 students—which would then made this research as a population research since in this case the research was conducted on a large scope of areas with all the subjects were made as samples. Statistic technique used in this research to manipulate and process data acquired from data gathering is a Spearman Rank’s Correlation. As from this research concluded, we could see that there is a 0.535 correlation between students perception towards schooling environment with learning motivation. Furthermore, we could also find out a positive correlation between academic emphasize aspect and expectation of success with learning motivation—which means that the higher perception those students had, the higher learning motivation built up inside them which would then resulted in higher expectation of success both from school authority and themselves.